A mixed-methods examination of public attitudes toward vascularized composite allograft donation and transplantation. (September 2022) - Gardiner, Heather M; Davis, Ellen E; Alolod, Gerard P; Sarwer, David B; Siminoff, Laura A
Background: This mixed-methods study examined the general public's knowledge and attitudes about vascularized composite allografts. The availability of these anatomical gifts to treat individuals with severe disfiguring injuries relies largely on decisions made by family members. If vascularized composite allograft transplantation is to become more readily available, the knowledge and beliefs of the general public must be explored to ensure vascularized composite allograft donation approaches adequately support the donation decision-making process. Methods: We conducted six focus groups with 53 members of the general public, which were audio-recorded for accuracy and transcribed. Before each session, participants completed a brief survey assessing donation-related knowledge, attitudes, and beliefs. Analysis of qualitative data entailed the constant comparison method in the development and application of a schema for thematic coding. Descriptive statistics and Spearman's rank coefficient were used in the analysis of the quantitative data. Results: Respondents were most knowledgeable about solid organ donation and least knowledgeable about vascularized composite allograft donation. Six major themes emerged: (1) strong initial reactions toward vascularized composite allografts, (2) limited knowledge of and reservations about vascularized composite allografts, (3) risk versus reward in receiving a vascularized composite allograft, (4) information needed to authorize vascularized composite allograft donation, (5) attitudes toward donation, and (6) mistrust of the organ donation system. Conclusion: The general public has low levels of knowledge and high levels of hesitation about vascularized composite allograft donation and transplantation. Education campaigns to familiarize the general public with vascularized composite allografts and specialized training for donation professionals to support informed family decision-making about vascularized composite allograft donation may address these issues.